Sociedade de garantia de crédito como uma solução na concessão de crédito para micro, pequenos e médios empresários no Oeste do Paraná - Plec, Otmar (2010)
Work carried out on a empirical research on the difficulties of Micro and Small Company in obtaining credit from the financial market and the establishment of a Credit Guarantee Organization in the Western Region of Paraná as a tool for facilitating access to credit from bank. The object of study is the Micro, Small and Medium Company- MSME and Financial Institutions of the Western Region of Paraná. Where 1250 questionnaires were analyzed of a total population of 48,350 companies and 23 financial institutions. The dissertation aims to contribute to the advancement of knowledge of the difficulties surrounding the MSMEs from the region and diagnose if the lack of guarantees and the asymmetry of information are inhibiting factors on getting resources from the banks. The conclusion of this study contributes to the academy to examine the feasibility of this new tool in helping the development of the region than in other countries has been highlighted as a facilitator and supporter of the SMEs as a transforming force in society and that has been fostered by SEBRAE together with various entities.